Tentang Volume Ini - Billy Kristanto (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2022)
Theology has a task to serve the faith accountability in discourse that places it in an applicative relationship with a cultural mandate, the politics and society development, and the good and beneficial ecumenical dialogue.